Local government shared services centers : management and organizations - Modrzyński, Paweł (Emerald points., 2020)
Built on independent research and financial audits of a number of newly created Shared Service Centers (SSCs) in Poland, Local Government Shared Services Centers: Management and Organizationis the first book to thoroughly examine the organization, development and effectiveness of the shared service market in the Polish public sector.